 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
If a/(b+c)+b/(c+a)+c/(a+b),then a2/(b+c)+b2/(c+a)+c2/(a+b)=?

```
4 years ago

```							LET A/B+C=-1,B/C+A=1,C/A+B=1 will satisfy this equation from above,a= -(b+c),......(1)b=c+a.....(2)c=a+b.....(3) now adding equation1,2,3a+b+c=2ab+c=a....(4) now a2/b+c=a*(a/b+c)=-a......(5) similarly b2/c+a=b...............(6)aandc2/a+b=c.......(7)  now adding equaation5,6,7we find desire value(a2/b+c)+( b2/c+a)+(c2/a+b)=-a+b+c...(8) from equaation 4b+c=a put value inequation 8-a+b+c= -a+a=0 hence proved
```
3 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions